A study of using tyre powder rubber as partially replacement of fine aggregate in concrete - Mahmood, Osamah Maged (2019)
The use of waste tire as a component in concrete has taken a great attention in engineering society. Sustainability was the first concern as well as properties of the product. Many researches have been done on the use of tires waste Rubber as a replacement of fine aggregate and course aggregate to produce environmentally sustainable concrete. This study is investigation on the performance of concrete using tyre rubber as partially replacement of fine aggregate. Three mixes of concrete are carried out with 0%, 5% and 10% level of replacement to investigate the effect of using tyre rubber in compressive strength, flexural strength, and ultra-pulse velocity test. In concrete production, Portland Composite cement, coarse aggregate, fine aggregate, water and tyre powder rubber waste are used as the materials in mixing process. The maximum size of coarse aggregate is 20 mm and the size of fine aggregate for this research is between 4.75 mm and 2.36 mm. The experiments conducted to compressive strength, flexural, ultra-pulse velocity respectively. In this research, slump test result of each batch is at range of 64-75 workability. Besides that, concrete with 0%, 5%, and 10% of tyre rubber replacement achieved compressive strength of 40.27, 29.13, and 26.15 N/mm2, respectively. While flexural strength is 5.648, 5.056, and 4.21, respectively. Results showed that strength of concrete reduced gradually with increasing percentage of tyre powder replacement. Results of ultra pules velocity with range of 3.58-4.17Km/s indicated that quality and integrity of concrete is good. Even though rubberized concrete mixture generally has a reduced compressive and flexural strength that may limit its use in certain structural applications, it possesses several desirable properties, such as lower density and higher toughness compared to conventional concrete.